Tonin Overexpression in Mice Diminishes Sympathetic Autonomic Modulation and Alters Angiotensin Type 1 Receptor Response - Jara, Zaira Palomino; Icimoto, Marcelo Yudi; Yokota, Rodrigo; Ribeiro, Amanda Aparecida; dos Santos, Fernando; Souza, Leandro Ezequiel de; Watanabe, Ingrid Kazue Mizuno; Franco, Maria do Carmo; Pesquero, Jorge Luiz; Irigoyen, Maria Claudia; Casarini, Dulce Elena (Frontiers in Medicine, 2019)
Background: Tonin, a serine-protease that forms Angiotensin II (AngII) from angiotensinogen, is increased in failing human heart samples. Increased blood pressure (BP) and decreased heart rate (HR) variabilities are associated with higher risk of cardiovascular morbidity. Losartan has been used to reduce hypertension and, therefore, lowers the risk of fatal and nonfatal cardiovascular events. Determination of tonin’s impact on BP and HR variabilities as well as the impact of losartan remain questions to be elucidated. Aim: Evaluation of cardiovascular autonomic profile in transgenic mice overexpressing the rat tonin enzyme TGM´(rton)) and the impact of AT1 receptor blocker, losartan. Methods: Male C57BL/6 (WT) and TGM’(rTon) mice were cannulated for recording BP for 30 min at baseline and 30 min after losartan injection (20 mg/kg). BP and HR variabilities were analyzed in time and frequency domain method. Low-frequency (LF) and high-frequency (HF) components were identified for sympathetic and parasympathetic modulations analysis. Ang I, AngII and Ang1-7 were quantified in the heart. The total enzymatic activity for AngI, AngII and Ang1-7 formation was evaluated in the heart and plasma . Results: At the baseline TGM’(rTon) exhibited higher BP, lower cardiac LF, higher cardiac HF, lower LF/HF and lower alpha index than wild type (WT). After losartan injection, TGM’(rTon) mice presented an additional decrease in cardiac LF and increase in HF compared to baseline and WT. In the vasculature, losartan caused decreased in BP and LF of systolic BP in WT mice compared to its baseline. A similar effect was observed in the BP of TGM’(rTon) mice; however, LF of systolic BP increased compared to baseline. AT1R receptor signaling has been altered in TGM’(rTon) mice, and the dynamics of the renin-angiotensin system kinetics changed, favoring production of Ang1-7. Conclusion: HR variability in TGM’(rTon) mice indicates high risk of morbidity, and sympathetic and parasympathetic modulation indicate low risk of morbidity. The low risk of morbidity could be the biased production of Ang1-7 in the heart and circulation; however, the altered response of AT1R in the TGM’(rTon) remains to be elucidated, as well as whether that signaling is pro-protection or pro-pathology.